MED-EL hearing solution registry: an examination of the strengths and limitations of a cochlear implant registry - Baumann, Uwe; Weissgerber, Tobias; Radeloff, Andreas; Koinig, Karin A.; Breu, Magdalena; Rinnofner, Jasmine; Lohnherr, Vera; Dazert, Stefan; Völter, Christiane; Anderson, Ilona; Müller, Joachim; Polterauer, Daniel (PLOS ONE, 2025)
There is a significant gap in routine clinical data concerning cochlear implant (CI) users, particularly regarding real-world outcomes. To address this, the present study focuses on the MED-EL Hearing Solution (MEHS) multicenter registry, which covers 5 clinics in Germany. Participants were users of a SONNET 2 or SONNET 2 EAS audio processor. Anonymized data that were routinely collected were extracted and analyzed by a third-party organization. Speech test outcomes (monosyllables and numbers), hours of daily use, self-perceived level of auditory benefit, and safety were assessed. Outcomes from 361 SONNET 2 (or SONNET 2 EAS) users, including 57 bilateral users, were extracted and analyzed. Speech test outcomes increased significantly from pre-operatively to 1 year of CI use in monosyllables (median 10.0% to 65.0%) and numbers (median 77.8% to 100.0%) (both p < 0.001). The majority (79%) of people used their device for at least 9 hours a day. The level of self-perceived auditory benefit was “moderate”. Safety was assessed as per participant self-report: 17 minor clinical events were reported, none were new or unresolved. The data obtained from the MEHS registry offers valuable real-life evidence from routine clinical evaluations, which can support clinicians in developing more informed guidelines and treatment plans. The SONNET 2 (EAS) is effective and safe to use. Registries have the potential to provide a wealth of data that can be used to improve hearing health care. However, the success of registries depends on consistent participation and adherence to standardized protocols by clinical centers. Variability in clinical practices, demographic factors, and reporting standards across centers poses significant challenges to achieving homogeneous and usable data.